2004
DOI: 10.1007/s00247-004-1189-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Doppler parameters of central versus intraparenchymal renal arteries in physiologically normal newborns

Abstract: Physiological data are presented that are necessary for the correct interpretation of neonatal Doppler US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…All our values of peak flow velocity, S/D ratio, RI, and PI were not different with advancing of gestational age and birth weight. Similar to our results, Pokharel et al 18 and Stavel et al 19 showed no statistical differences between peak flow velocity and RI measured in renal arteries of 2 groups in the first 5 days of life. A decline of the RI in the renal artery from the last trimester of pregnancy to the sixth month of life was shown by Andriani et al 3 They examined 32 fetuses in the last trimester of pregnancy and 30 neonates aged 0 to 1 month.…”
Section: Discussionsupporting
confidence: 92%
“…All our values of peak flow velocity, S/D ratio, RI, and PI were not different with advancing of gestational age and birth weight. Similar to our results, Pokharel et al 18 and Stavel et al 19 showed no statistical differences between peak flow velocity and RI measured in renal arteries of 2 groups in the first 5 days of life. A decline of the RI in the renal artery from the last trimester of pregnancy to the sixth month of life was shown by Andriani et al 3 They examined 32 fetuses in the last trimester of pregnancy and 30 neonates aged 0 to 1 month.…”
Section: Discussionsupporting
confidence: 92%
“…7,14 Our results did not show any correlation between the parameters of renal vascular resistance and birth weight or weight deficit in SGA infants. Stavel et al 19 investigated AGA term newborns with Doppler sonography and, similar to Zibolen, 20 observed a decrease in RI values from the center to the periphery of the kidney. They also established reference values of Doppler parameters of renal circulation in healthy neonates.…”
Section: Discussionmentioning
confidence: 83%